IMPLEMENTASI METODE PEMBIASAAN DALAM PENGEMBANGAN MORAL KEAGAMAAN AUD KELOMPOK B DI RA AN NAJWAN DESA KEBUN BALOK KABUPATEN LANGKAT - Halimah Halimah; Rustam Rustam; Zulfahmi Lubis (Universitas Islam Negeri Sumatera Utara, 2019)
Moral is the values and norms that become a guideline for children or someone in regulating their behavior. Therefore, moral is very important to developed in early childhood. One way to develop morals is applied in RA An-Najwan is a habitual method to educating children to thinking, behaving and act according to the teachings of Islam. Thus, this study was conducted to determine the development of religious morals, the application of habituation methods, as well as the supporting and inhibiting factors. This study is a qualitative type using observation, interview, and documentation techniques to obtain data. The subjects in this study were the principal, teacher, and children’s group B aged. The results show that: (1) religion moral development of early childhood group B in RA An Najwan is good categorized, seen from the ability of children who are able to implement religious moral values such as: greeting, independence, responsibility, patience in waiting, enthusiastic worship, want to share; (2) supporting factors are the ability of teachers and community enthusiasm to the school, while the inhibiting factor is parents who prefer their children to be academically smart and there are still children who are always helped by parents.